High-compaction-density positive electrode material as well as preparation method and application thereof

Through multi-carbon source coating technology and high-temperature sintering method, the compaction density of the cathode material is improved, the problem of low compaction density of the cathode material in the prior art is solved, and the specific capacity and energy density of lithium-ion batteries are improved, while reducing production costs.

CN119905538APending Publication Date: 2025-04-29LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311417556.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The compaction density of the existing positive electrode materials is low, which limits the increase in volume energy density of lithium-ion batteries. The existing compaction density enhancement methods consume high energy, which is not conducive to the practical application of materials.

Method used

By using multiple carbon sources of different particle sizes to coat the positive electrode active material, the smoothness of the material surface and the grade between particles are improved, the particle size of the particles is increased, and the carbon cladding layer is formed through high-temperature sintering to improve the compaction density of the material.

Benefits of technology

It effectively improves the compaction density of the positive electrode material, improves the specific capacity and energy density of lithium-ion batteries, and reduces production costs, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905538A_ABST
    Figure CN119905538A_ABST
Patent Text Reader

Abstract

The invention discloses a high-compaction-density positive electrode material and a preparation method and application thereof.The preparation method comprises the steps that a positive electrode active material, a first carbon source material, a second carbon source material and a solvent are placed in stirring equipment to be stirred and evenly mixed, and a mixed solution is obtained; transferring the mixed solution into drying equipment for drying treatment to obtain precursor powder; and transferring the precursor powder into heat treatment equipment for high-temperature sintering treatment, and cooling to room temperature to obtain the high-compaction-density positive electrode material. Wherein the particle size D50 of the first carbon source material is 50-800 nm, the particle size D50 of the second carbon source material is 10-500 nm, and the particle size of the second carbon source material is smaller than that of the first carbon source material; and the compaction density of the high-compaction-density positive electrode material is increased by 0.3%-12% relative to the compaction density of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a high compaction density positive electrode material and a preparation method and application thereof. Background Art

[0002] With the large-scale application of lithium-ion batteries in mobile communications, electric vehicles, renewable energy and other fields, cathode materials, as an important component of lithium-ion batteries, play a vital role in the development of the lithium-ion battery industry.

[0003] During the manufacturing process of lithium-ion power batteries, compaction density has a great influence on battery performance. Generally speaking, the greater the compaction density, the higher the battery capacity can be. The compaction density is not only related to the size and density of the particles, but also to the gradation of the particles.

[0004] The existing positive electrode materials have the disadvantage of low compaction density, which greatly limits the improvement of the volume energy density of lithium-ion batteries. Improving the compaction density of positive electrode materials is a very effective method to increase the capacity of lithium-ion batteries. However, the compaction density improvement methods currently used generally have the problem of high energy consumption, which is not conducive to the practical application of materials or affects the subsequent pulping process of materials. Therefore, it is necessary to develop a low-cost method to effectively improve the positive electrode material. Summary of the invention

[0005] The purpose of the present invention is to provide a high compaction density positive electrode material and its preparation method and application to solve the existing problem. The present invention adopts a method of coating positive electrode active materials with multiple carbon sources to improve the compaction density, mainly using multiple carbon sources with different particle sizes to improve the smoothness of the material surface, improve the grading between particles, increase the particle size of primary particles, improve the coated carbon source, and thus improve the compaction density of the material.

[0006] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a high compaction density positive electrode material, the preparation method comprising:

[0007] Placing the positive electrode active material, the first carbon source material, the second carbon source material and the solvent in a stirring device, stirring and mixing them evenly to obtain a mixed solution with a solid content of 15% to 60%;

[0008] The mixed solution is transferred to a drying device for drying to obtain a precursor powder;

[0009] The precursor powder is transferred to a heat treatment device, heated to 300°C-950°C at a heating rate of 1°C / min-15°C / min in a protective gas environment, sintered at high temperature for 6 hours-15 hours, and cooled to room temperature to obtain a high compaction density positive electrode material;

[0010] Among them, the particle size D of the first carbon source material 50 The particle size D of the second carbon source material is 50nm-800nm. 50 The particle size of the second carbon source material is 10 nm-500 nm, and the particle size of the second carbon source material is smaller than the particle size of the first carbon source material;

[0011] The particle size D of the high compaction density positive electrode material 50 0.4μm-55μm;

[0012] The compaction density of the high compaction density positive electrode material is increased by 0.3%-12% relative to the compaction density of the positive electrode active material.

[0013] Preferably, the positive electrode active material includes: one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium titanate, and nickel cobalt manganese ternary material; the mass of the positive electrode active material accounts for 15%-60% of the total mass of the mixed solution; the particle size D of the positive electrode active material is 50 0.3μm-50μm;

[0014] The first carbon source material includes: one or more of glucose, sucrose, glycogen, asphalt, hard carbon, fructose, starch, vitamin C, cellulose acetate, citric acid, polyvinyl alcohol, polyethylene glycol, polyethylene oxide, phenolic resin, polyaniline, and polyvinyl pyrrolidone; the mass of the first carbon source material accounts for 1%-10% of the total mass of the mixed solution;

[0015] The second carbon source material includes: one or more of graphite, graphene, acetylene black, activated carbon, carbon black, carbon fiber, mesoporous carbon, carbon nanotubes, and carbon molecular sieves; the mass of the second carbon source material accounts for 1%-5% of the total mass of the mixed solution;

[0016] The solvent comprises: one or more of N-methylpyrrolidone, deionized water, acetone, ethanol, chloroform, benzene, styrene and tetrahydrofuran; the mass of the solvent accounts for 35%-70% of the total mass of the mixed solution.

[0017] Preferably, the stirring equipment includes: one or more of a VC high-efficiency mixer, a planetary mixer, a vertical stirring tank, and a high-energy ball mill;

[0018] The rotation speed of the stirring device is 50r / min-600r / min, and the stirring time is 1 hour-8 hours.

[0019] Preferably, the drying equipment includes: one or more of a spray dryer, a blast drying oven, a vacuum drying oven, a rotary evaporation dryer, and an oil bath pot; the drying treatment temperature is 60°C-300°C; and the drying time is 6 hours-24 hours.

[0020] Preferably, the protective gas includes: one or more of nitrogen, argon, and helium;

[0021] The heat treatment equipment includes: any one of a box furnace, a tube furnace, a push plate furnace, a roller kiln, and a rotary kiln.

[0022] In a second aspect, an embodiment of the present invention provides a high compaction density positive electrode material prepared by the preparation method described in the first aspect, wherein the high compaction density positive electrode material comprises: a positive electrode active material, and a carbon coating layer coated on the outer surface of the positive electrode active material; the carbon coating layer comprises first carbon particles and second carbon particles;

[0023] Wherein, the particle size of the first carbon particles is larger than the particle size of the second carbon particles; the first carbon particles are irregular in shape;

[0024] The particle size D of the high compaction density positive electrode material 50 0.4μm-55μm;

[0025] The compaction density of the high compaction density positive electrode material is increased by 0.3%-12% relative to the compaction density of the positive electrode active material.

[0026] Preferably, the positive electrode active material particles include: particles of one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium titanate, and nickel-cobalt-manganese ternary material;

[0027] The thickness of the carbon coating layer is 0.1 μm-5 μm;

[0028] The average particle size of the first carbon particles is 50nm-800nm;

[0029] The average particle size D of the second carbon particles 50 It is 10nm-500nm.

[0030] Preferably, the mass of the positive electrode active material accounts for 25%-90% of the total mass of the high compaction density positive electrode material;

[0031] The mass of the first carbon particles accounts for 1% to 15% of the total mass of the high compaction density positive electrode material;

[0032] The mass of the second carbon particles accounts for 1%-12% of the total mass of the high compaction density positive electrode material.

[0033] In a third aspect, an embodiment of the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the high compaction density positive electrode material described in the second aspect.

[0034] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in the third aspect.

[0035] The embodiment of the present invention provides a high compaction density positive electrode material and a preparation method and application thereof. By uniformly mixing and drying the materials, two carbon source materials with different particle sizes and the positive electrode active material are evenly mixed and distributed. The particles of the second carbon source material with a small particle size fill the gaps between the particles of the first carbon source material to form an initial coating layer of the positive electrode active material. After high-temperature sintering, the particles diffuse and combine to form a carbon coating layer on the surface of the positive electrode active material. During the temperature change process of high-temperature sintering, the first carbon source material undergoes low-temperature melting and high-temperature carbonization to form particles, and the particle size grading of the first carbon particles, the second carbon particles and the positive electrode active material is formed. At the same time, during the low-temperature melting process, the first carbon source material forms irregularly shaped first carbon particles, which can improve the concave and convex parts of the coating layer and improve the smoothness of the particles, thereby improving the compaction density of the material. The high compaction density positive electrode material of the present invention is applied to lithium-ion batteries to improve the specific capacity of lithium-ion batteries, thereby improving the energy density of lithium-ion batteries.

[0036] The preparation method provided by the embodiment of the present invention is simple to operate, low in cost, and applicable to large-scale production, and has practical significance for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0038] Figure 1 It is a flow chart of a method for preparing a high compaction density positive electrode material provided in an embodiment of the present invention.

[0039] Figure 2 It is a schematic diagram of the structure of the high compaction density positive electrode material provided by an embodiment of the present invention before and after high temperature sintering.

[0040] Figure 3 It is a charge and discharge curve diagram of the button battery assembled in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0042] The present invention provides a method for preparing a high compaction density positive electrode material. Figure 1 As shown, the specific steps include:

[0043] Step 110, placing the positive electrode active material, the first carbon source material, the second carbon source material and the solvent in a stirring device, stirring and mixing them evenly to obtain a mixed solution with a solid content of 15%-60%;

[0044] The positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium titanate, and nickel cobalt manganese ternary material; the mass of the positive electrode active material accounts for 15%-60% of the total mass of the mixed solution; the particle size D of the positive electrode active material 50 0.3μm-50μm;

[0045] The first carbon source material includes: one or more of glucose, sucrose, glycogen, asphalt, hard carbon, fructose, starch, vitamin C, cellulose acetate, citric acid, polyvinyl alcohol, polyethylene glycol, polyethylene oxide, phenolic resin, polyaniline, and polyvinyl pyrrolidone; the mass of the first carbon source material accounts for 1%-10% of the total mass of the mixed solution;

[0046] The second carbon source material includes: one or more of graphite, graphene, acetylene black, activated carbon, carbon black, carbon fiber, mesoporous carbon, carbon nanotubes, and carbon molecular sieves; the mass of the second carbon source material accounts for 1%-5% of the total mass of the mixed solution;

[0047] The particle size D of the first carbon source material 50 The particle size D of the second carbon source material is 50nm-800nm. 50 The particle size of the second carbon source material is 10 nm to 500 nm, and the particle size of the second carbon source material is smaller than the particle size of the first carbon source material;

[0048] The solvent includes: one or more of N-methylpyrrolidone, deionized water, acetone, ethanol, chloroform, benzene, styrene, and tetrahydrofuran; the mass of the solvent accounts for 35%-70% of the total mass of the mixed solution;

[0049] The stirring equipment includes: one or more of VC high-efficiency mixer, planetary mixer, vertical stirring tank, high-energy ball mill; the rotation speed of the stirring equipment is 50r / min-600r / min, and the stirring time is 1 hour-8 hours.

[0050] Step 120, transferring the mixed solution to a drying device for drying to obtain a precursor powder;

[0051] The drying equipment includes: one or more of a spray dryer, a blast drying oven, a vacuum drying oven, a rotary evaporation dryer, and an oil bath pot; the drying temperature is 60°C-300°C; and the drying time is 6 hours-24 hours.

[0052] Step 130, transferring the precursor powder to a heat treatment device, heating the temperature to 300°C-950°C at a heating rate of 1°C / min-15°C / min in a protective gas environment, high-temperature sintering for 6 hours-15 hours, and cooling to room temperature to obtain a high compaction density positive electrode material;

[0053] The protective gas includes one or more of nitrogen, argon and helium;

[0054] The heat treatment equipment includes: any one of box furnace, tube furnace, push plate furnace, roller kiln and rotary kiln.

[0055] In the material mixing stage 110 and the drying stage 120 of the present invention, particles of different particle sizes are mixed and distributed evenly, and particles of the second carbon source material with small particle size fill the gaps between the particles of the first carbon source material to form an initial coating layer of the positive electrode active material. Then, in the high-temperature sintering stage of step 130, the particles diffuse and combine to form a carbon coating layer on the surface of the positive electrode active material.

[0056] The high-temperature sintering process of the present invention is to heat the temperature to 300°C-950°C at a heating rate of 1°C / min-15°C / min. The first carbon source material undergoes low-temperature melting and high-temperature carbonization to form particles, and the particle size grading of the first carbon particles, the second carbon particles and the positive electrode active material is formed. At the same time, during the low-temperature melting process, the first carbon source material forms irregularly shaped first carbon particles, which can improve the concave and convex parts of the coating layer and improve the smoothness of the particles, thereby improving the compaction density of the material.

[0057] The embodiment of the present invention provides a high compaction density positive electrode material prepared by the above preparation method, comprising: a positive electrode active material, and a carbon coating layer coated on the outer surface of the positive electrode active material; the carbon coating layer comprises a first carbon particle and a second carbon particle; the particle size of the first carbon particle is larger than the particle size of the second carbon particle, and the first carbon particle is irregular in shape; the average particle size of the first carbon particle is 50nm-800nm; the average particle size D of the second carbon particle is 50 The carbon coating layer has a thickness of 10 nm to 500 nm and a thickness of 0.1 μm to 5 μm.

[0058] The particle size D of the high compaction density positive electrode material provided in the embodiment of the present invention is 50The compaction density of the high compaction density positive electrode materials prepared from different positive electrode active materials is different. The compaction density of the high compaction density positive electrode material of the present invention is increased by 0.3%-12% relative to the compaction density of the positive electrode active material, preferably by 0.3%-9%.

[0059] The positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium titanate, and nickel-cobalt-manganese ternary material; the first carbon particles and the second carbon particles are both single carbon.

[0060] For example, when the positive electrode active material is lithium iron phosphate, its compaction density is 2.2 g / cm 3 -2.3g / cm 3 The compaction density of the prepared high compaction density positive electrode material is 2.21g / cm 3 -2.58g / cm 3 .

[0061] When the positive electrode active material is lithium cobalt oxide, its compaction density is 4.1 g / cm 3 -4.3g / cm 3 The compaction density of the prepared high compaction density positive electrode material is 4.11 g / cm 3 -4.82g / cm 3 .

[0062] When the positive electrode active material is a nickel-cobalt-manganese ternary material, its compaction density is 3.4 g / cm 3 -3.7g / cm 3 The compaction density of the prepared high compaction density positive electrode material is 3.41g / cm 3 -4.14g / cm 3 .

[0063] When the positive electrode active material is lithium manganese oxide, its compaction density is 2.9 g / cm 3 -3.2g / cm 3 The compaction density of the prepared high compaction density positive electrode material is 2.91g / cm 3 -3.58g / cm 3 .

[0064] The content of each component in the high compaction density positive electrode material provided by the embodiment of the present invention is specifically as follows: the mass of the positive electrode active material accounts for 25%-90% of the total mass of the high compaction density positive electrode material; the mass of the first carbon particles accounts for 1%-15% of the total mass of the high compaction density positive electrode material; the mass of the second carbon particles accounts for 1%-12% of the total mass of the high compaction density positive electrode material.

[0065] The structure of the positive electrode active material and the carbon coating layer before high temperature sintering of the present invention and the structure of the positive electrode active material and the carbon coating layer in the high compaction density positive electrode material obtained after high temperature sintering are shown in FIG. Figure 2 As shown, it can be seen that before high-temperature sintering, the first carbon source material and the second carbon source material adhere to the surface of the positive electrode active material to form an initial coating layer, the particle size of the second carbon source material is smaller than that of the first carbon source material, and the second carbon source material is dispersed in the gaps between the particles of the first carbon source material; after high-temperature sintering, the first carbon source material and the second carbon source material are carbonized to form first carbon particles and second carbon particles respectively, the first carbon particles are irregular in shape, and the average particle size of the second carbon particles is smaller than the average particle size of the first carbon particles.

[0066] The high compaction density positive electrode material prepared by the above preparation method of the present invention can be used to prepare positive electrode slurry together with a conductive agent and a binder, and then coated on a positive electrode collector and baked and dried to obtain a positive electrode plate. The positive electrode plate can be assembled into a lithium-ion battery with a negative electrode plate, an electrolyte or a solid electrolyte, and a separator.

[0067] The above-mentioned lithium-ion battery includes, but is not limited to: any one of a liquid lithium-ion battery, a condensed lithium-ion battery, a polymer lithium-ion battery or an all-solid-state lithium-ion battery.

[0068] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the high compaction density positive electrode material of the present invention are respectively described below with multiple specific examples.

[0069] Example 1

[0070] This embodiment provides a preparation process and performance test of a high compaction density positive electrode material, and the specific process is as follows:

[0071] (1) The particle size D 50 The particle size of lithium iron phosphate is 2.1 μm. 50 The glucose particle size is 249.2nm, D 50 The particle size D is 263.7 nm. 50 The carbon nanotubes with a diameter of 32.9 nm and deionized water are placed in a high-energy ball mill and mixed by ball milling and stirring to obtain a mixed solution with a solid content of 45%.

[0072] (2) The mixed solution was introduced into a spray dryer at a rate of 20 ml / min, and the air inlet temperature of the spray dryer was controlled to be 260° C. and the air outlet temperature was controlled to be 130° C. to obtain a precursor powder.

[0073] (3) The precursor powder is transferred to a box furnace, heated to 800°C at a rate of 5°C / min in an argon atmosphere, and sintered for 8 hours, and then cooled to room temperature to obtain a high compaction density positive electrode material.

[0074] The high compaction density positive electrode material prepared in the embodiment of the present invention is used to prepare the positive electrode sheet and assemble it into a button cell for testing. The preparation process and the testing process are as follows:

[0075] Preparation of positive electrode sheet: The high compaction density positive electrode material prepared in this embodiment, polyvinylidene fluoride (PVDF), and conductive carbon black (SP) are homogenized into a slurry in a mass ratio of 93:5:2, then coated on the surface of aluminum foil, and vacuum dried at 80°C for 30 minutes to prepare a positive electrode sheet.

[0076] The compaction density test of the material is carried out through the positive electrode sheet: take the positive electrode sheet prepared in Example 1 and the aluminum foil without positive electrode active material, cut off a piece of each area with a circular cutter, measure the thickness and weigh and record, adjust the roller press pressure to 12Mpa to roll the positive electrode sheet, and test and record the thickness of the electrode sheet after rolling. The difference between the weight of the electrode sheet and the aluminum foil is divided by the area to calculate the surface density; the surface density is divided by the thickness difference before and after rolling, which is the compaction density. Specific compaction density data are shown in Table 1.

[0077] Assembly of button cells: A positive electrode sheet coated with the high compaction density positive electrode material prepared in this example, a polypropylene PP separator, a graphite negative electrode sheet and a 1M Li PF6 electrolyte are assembled into a button cell using conventional methods.

[0078] The button battery test method is: charge at a constant current rate of 0.1C to a voltage of 4.2V, then charge at a constant voltage of 4.2V to 0.02C, then let it stand for 5 minutes, and then discharge at a constant current rate of 0.1C to a voltage of 2.5V. Perform the first week of charge and discharge test. The test charge and discharge curve is as follows: Figure 3 As shown; the first discharge specific capacity data of the tested batteries are summarized in Table 1.

[0079] Example 2

[0080] This embodiment provides a preparation process and performance test of a high compaction density positive electrode material, and the specific process is as follows:

[0081] (1) The particle size D 50 The lithium iron phosphate particle size is 1.4 μm. 50 The particle size of sucrose is 216.2 nm, and the particle size D 50 The particle size of polyvinyl pyrrolidone is 224.6 nm. 50 The mesoporous carbon with a particle size of 31.3 nm and deionized water are placed in a planetary mixer for mixing and stirring to obtain a mixed solution with a solid content of 40%.

[0082] (2) The mixed solution was introduced into a spray dryer at a rate of 15 ml / min, and the air inlet temperature of the spray dryer was controlled to be 240° C. and the air outlet temperature was controlled to be 80° C. to obtain a precursor powder.

[0083] (3) The precursor powder is transferred to a box furnace, heated to 750°C at 5°C / min in an argon atmosphere, and sintered for 8 hours, and then cooled to room temperature to obtain a high compaction density positive electrode material.

[0084] The high compaction density positive electrode material prepared in the embodiment of the present invention is used to prepare a positive electrode sheet and perform a compaction density test. The preparation process and the test process are the same as those in Example 1. The specific compaction density data are detailed in Table 1.

[0085] The positive electrode sheet was prepared using the high compaction density positive electrode material prepared in the embodiment of the present invention and assembled into button cells for testing. The battery assembly and testing methods were the same as those in Example 1. The first discharge specific capacity data of the test cells are summarized in Table 1.

[0086] Example 3

[0087] This embodiment provides a preparation process and performance test of a high compaction density positive electrode material, and the specific process is as follows:

[0088] (1) The particle size D 50 The particle size D is 1.8 μm. 50 The starch particle size D is 232.6 nm. 50 The phenolic resin with a particle size of 228.5 nm 50 The carbon nanotubes with a diameter of 39.2 nm and deionized water are placed in a high-energy ball mill and mixed by ball milling and stirring to obtain a mixed solution with a solid content of 38%.

[0089] (2) The mixed solution was transferred to a forced air drying oven and dried at 120° C. to obtain a precursor powder.

[0090] (3) The precursor powder is transferred to a rotary furnace, heated to 800°C at a rate of 5°C / min in an argon atmosphere for high-temperature sintering for 6 hours, and cooled to room temperature to obtain a high compaction density positive electrode material.

[0091] The high compaction density positive electrode material prepared in the embodiment of the present invention is used to prepare a positive electrode sheet and perform a compaction density test. The preparation process and the test process are the same as those in Example 1. The specific compaction density data are detailed in Table 1.

[0092] The positive electrode sheet was prepared using the high compaction density positive electrode material prepared in the embodiment of the present invention and assembled into button cells for testing. The battery assembly and testing methods were the same as those in Example 1. The first discharge specific capacity data of the test cells are summarized in Table 1.

[0093] Example 4

[0094] This embodiment provides a preparation process and performance test of a high compaction density positive electrode material, and the specific process is as follows:

[0095] (1) The particle size D 50 The particle size D of lithium cobalt oxide is 12.2 μm 50 The particle size of sucrose is 432.6 nm, and the particle size D 50 The phenolic resin with a particle size of 432.6 nm and a particle size D 50 The carbon nanotubes with a diameter of 36.2 nm and deionized water are placed in a high-energy ball mill and mixed by ball milling and stirring to obtain a mixed solution with a solid content of 30%.

[0096] (2) The mixed solution was transferred to a forced air drying oven and dried at 140° C. to obtain a precursor powder.

[0097] (3) The precursor powder is transferred to a box furnace, then to a tube furnace, and sintered at 850°C at a rate of 5°C / min in an argon atmosphere for 6 hours, and then cooled to room temperature to obtain a high compaction density positive electrode material.

[0098] The high compaction density positive electrode material prepared in the embodiment of the present invention is used to prepare the positive electrode sheet and assemble it into a button cell for testing. The preparation process and the testing process are as follows:

[0099] Preparation of positive electrode sheet: The high compaction density positive electrode material prepared in this embodiment, polyvinylidene fluoride (PVDF), and conductive carbon black (SP) are homogenized into a slurry in a mass ratio of 93:5:2, then coated on the surface of aluminum foil, and vacuum dried at 80°C for 30 minutes to prepare a positive electrode sheet.

[0100] The positive electrode sheet was tested for compaction density: the positive electrode sheet prepared in this embodiment and the aluminum foil without positive electrode active material were cut off with a circular cutter, the thickness was measured and weighed, and the pressure of the roller press was adjusted to 12 MPa to roll the positive electrode sheet, and the thickness of the sheet after rolling was tested and recorded. The difference between the weight of the sheet and the aluminum foil was divided by the area to calculate the surface density; the surface density was divided by the thickness difference before and after rolling to obtain the compaction density. The specific compaction density data is shown in Table 1.

[0101] Assembly of button cells: A positive electrode sheet coated with the high compaction density positive electrode material prepared in this embodiment, a polypropylene PP separator, a graphite negative electrode sheet and an electrolyte of 1 mol / L Li PF6 (the solvent is ethylene carbonate EC and dimethyl carbonate DEC in a volume ratio of 1:1) are assembled into button cells using conventional methods.

[0102] The button cell test method is as follows: charge at a constant current rate of 0.1C to a voltage of 4.4V, then charge at a constant voltage of 4.4V to 0.02C, then let stand for 5 minutes, and then discharge at a constant current rate of 0.1C to a voltage of 2.75V for the first week of charge and discharge test. The first discharge specific capacity data of the test battery are summarized in Table 1.

[0103] The high compaction density positive electrode material prepared in the embodiment of the present invention is used to prepare a positive electrode sheet and perform a compaction density test. The preparation process and the test process are the same as those in Example 1. The specific compaction density data are detailed in Table 1.

[0104] The positive electrode sheet was prepared using the high compaction density positive electrode material prepared in the embodiment of the present invention and assembled into button cells for testing. The battery assembly and testing methods were the same as those in Example 1. The first discharge specific capacity data of the test cells are summarized in Table 1.

[0105] Example 5

[0106] This embodiment provides a preparation process and performance test of a high compaction density positive electrode material, and the specific process is as follows:

[0107] (1) The particle size D 50 The particle size D of lithium cobalt oxide is 13.1 μm 50 The particle size of sucrose is 464.6 nm, and the particle size D 50 The particle size D of polyvinyl alcohol is 457.9 nm. 50 The carbon fiber with a diameter of 53.8 nm and deionized water are placed in a high-energy ball mill and mixed by ball milling to obtain a mixed solution with a solid content of 35%.

[0108] (2) The mixed solution was introduced into a spray dryer at a rate of 15 ml / min, and the air inlet temperature of the spray dryer was controlled to be 260° C. and the air outlet temperature was controlled to be 120° C. to obtain a precursor powder.

[0109] (3) The precursor powder is transferred to a box furnace, heated to 730°C at a rate of 5°C / min in an argon atmosphere, and sintered at high temperature for 12 hours, and then cooled to room temperature to obtain a high compaction density positive electrode material.

[0110] The high compaction density positive electrode material prepared in the embodiment of the present invention is used to prepare a positive electrode sheet and perform a compaction density test. The preparation process and the test process are the same as those in Example 1. The specific compaction density data are detailed in Table 1.

[0111] The positive electrode sheet prepared in the comparative example of the present invention was assembled into a button cell for testing. The battery assembly and testing methods were the same as those in Example 4. The first discharge specific capacity data of the tested battery are summarized in Table 1.

[0112] Example 6

[0113] This embodiment provides a preparation process and performance test of a high compaction density positive electrode material, and the specific process is as follows:

[0114] (1) The particle size D 50 The particle size D of lithium cobalt oxide is 12.6 μm 50 The starch particle size D is 489.4 nm. 50 The phenolic resin with a particle size of 401.3 nm and a particle size of D 50 The carbon nanotubes with a diameter of 41.4 nm and deionized water are placed in a vertical stirring tank for mixing and stirring to obtain a mixed solution with a solid content of 30%.

[0115] (2) The mixed solution was transferred to a forced air drying oven and dried at 120° C. to obtain a precursor powder.

[0116] (3) The precursor powder is transferred to a box furnace, heated to 900°C at a rate of 5°C / min in an argon atmosphere, and sintered for 6 hours, and then cooled to room temperature to obtain a high compaction density positive electrode material.

[0117] The high compaction density positive electrode material prepared in the embodiment of the present invention is used to prepare a positive electrode sheet and perform a compaction density test. The preparation process and the test process are the same as those in Example 1. The specific compaction density data are detailed in Table 1.

[0118] The positive electrode sheet prepared in the comparative example of the present invention was assembled into a button cell for testing. The battery assembly and testing methods were the same as those in Example 4. The first discharge specific capacity data of the tested battery are summarized in Table 1.

[0119] In order to better illustrate the effects of the embodiments of the present invention, Comparative Example 1 is compared with Embodiments 1-3, and Comparative Example 2 is compared with Embodiments 4-6.

[0120] Comparative Example 1

[0121] In this comparative example, lithium iron phosphate with an average particle size of 1.4 μm was selected to prepare a positive electrode sheet according to the method of Example 1. The compaction density of the electrode sheet was tested according to the test method of Example 1, and the compaction density data obtained are shown in Table 1.

[0122] The positive electrode sheet prepared in the comparative example of the present invention was assembled into a button cell for testing. The battery assembly and testing methods were the same as those in Example 1. The first discharge specific capacity data of the tested battery are summarized in Table 1.

[0123] Comparative Example 2

[0124] In this comparative example, lithium cobalt oxide with an average particle size of 12.7 μm was selected to prepare a positive electrode sheet according to the method of Example 4. The compaction density of the electrode sheet was tested according to the test method of Example 4, and the compaction density data was shown in Table 1.

[0125] The positive electrode sheet prepared in the comparative example of the present invention was assembled into a button cell for testing. The battery assembly and testing methods were the same as those in Example 4. The first discharge specific capacity data of the tested battery are summarized in Table 1.

[0126] Table 1 is a summary of the compaction density of the positive electrode sheets of Examples 1-6 and Comparative Examples 1-2 and the first discharge specific capacity test data of the assembled batteries:

[0127]

[0128] Table 1

[0129] From the test data in Table 1, it can be seen that the compaction density of Examples 1-3 is higher than that of Comparative Example 1, and the corresponding first discharge specific capacity is higher than that of Comparative Example 1, indicating that the high compaction density positive electrode material formed by coating lithium iron phosphate with multiple carbon sources effectively improves the specific capacity of the lithium ion battery. The compaction density of Examples 4-6 is higher than that of Comparative Example 2, and the corresponding first discharge specific capacity is higher than that of Comparative Example 2, indicating that the high compaction density positive electrode material formed by coating lithium cobalt oxide with multiple carbon sources effectively improves the specific capacity of the lithium ion battery.

[0130] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high compaction density positive electrode material, characterized in that: The preparation method comprises: Placing the positive electrode active material, the first carbon source material, the second carbon source material and the solvent in a stirring device, stirring and mixing them evenly to obtain a mixed solution with a solid content of 15% to 60%; The mixed solution is transferred to a drying device for drying to obtain a precursor powder; The precursor powder is transferred to a heat treatment device, heated to 300°C-950°C at a heating rate of 1°C / min-15°C / min in a protective gas environment, sintered at high temperature for 6 hours-15 hours, and cooled to room temperature to obtain a high compaction density positive electrode material; Among them, the particle size D of the first carbon source material 50 The particle size D of the second carbon source material is 50nm-800nm. 50 The particle size of the second carbon source material is 10 nm-500 nm, and the particle size of the second carbon source material is smaller than the particle size of the first carbon source material; The particle size D of the high compaction density positive electrode material 50 0.4μm-55μm; The compaction density of the high compaction density positive electrode material is increased by 0.3%-12% relative to the compaction density of the positive electrode active material.

2. The preparation method according to claim 1, characterized in that: The positive electrode active material includes: one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium titanate, and nickel cobalt manganese ternary material; the mass of the positive electrode active material accounts for 15%-60% of the total mass of the mixed solution; the particle size D of the positive electrode active material 50 0.3μm-50μm; The first carbon source material includes: one or more of glucose, sucrose, glycogen, asphalt, hard carbon, fructose, starch, vitamin C, cellulose acetate, citric acid, polyvinyl alcohol, polyethylene glycol, polyethylene oxide, phenolic resin, polyaniline, and polyvinyl pyrrolidone; the mass of the first carbon source material accounts for 1%-10% of the total mass of the mixed solution; The second carbon source material includes: one or more of graphite, graphene, acetylene black, activated carbon, carbon black, carbon fiber, mesoporous carbon, carbon nanotubes, and carbon molecular sieves; the mass of the second carbon source material accounts for 1%-5% of the total mass of the mixed solution; The solvent comprises: one or more of N-methylpyrrolidone, deionized water, acetone, ethanol, chloroform, benzene, styrene and tetrahydrofuran; the mass of the solvent accounts for 35%-70% of the total mass of the mixed solution.

3. The preparation method according to claim 1, characterized in that: The mixing equipment includes: one or more of a VC high-efficiency mixer, a planetary mixer, a vertical mixing tank, and a high-energy ball mill; The rotation speed of the stirring device is 50r / min-600r / min, and the stirring time is 1 hour-8 hours.

4. The preparation method according to claim 1, characterized in that: The drying equipment includes: one or more of a spray dryer, a blast drying oven, a vacuum drying oven, a rotary evaporation dryer, and an oil bath pot; the drying treatment temperature is 60° C.-300° C.; and the drying time is 6 hours-24 hours.

5. The preparation method according to claim 1, characterized in that: The protective gas includes: one or more of nitrogen, argon and helium; The heat treatment equipment includes: any one of a box furnace, a tube furnace, a push plate furnace, a roller kiln, and a rotary kiln.

6. A high compaction density positive electrode material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The high compaction density positive electrode material comprises: a positive electrode active material, and a carbon coating layer coated on the outer surface of the positive electrode active material; the carbon coating layer comprises first carbon particles and second carbon particles; Wherein, the particle size of the first carbon particles is larger than the particle size of the second carbon particles; the first carbon particles are irregular in shape; The particle size D of the high compaction density positive electrode material 50 0.4μm-55μm; The compaction density of the high compaction density positive electrode material is increased by 0.3%-12% relative to the compaction density of the positive electrode active material.

7. The high compaction density positive electrode material according to claim 6, characterized in that: The positive electrode active material particles include: particles of one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium titanate, and nickel-cobalt-manganese ternary material; The thickness of the carbon coating layer is 0.1 μm-5 μm; The average particle size of the first carbon particles is 50nm-800nm; The average particle size D of the second carbon particles 50 It is 10nm-500nm.

8. The high compaction density positive electrode material according to claim 6, characterized in that: The mass of the positive electrode active material accounts for 25%-90% of the total mass of the high compaction density positive electrode material; The mass of the first carbon particles accounts for 1% to 15% of the total mass of the high compaction density positive electrode material; The mass of the second carbon particles accounts for 1%-12% of the total mass of the high compaction density positive electrode material.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the high compaction density positive electrode material described in claims 6-8 above.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as described in claim 9 above.